Pengaruh Pemberian Rebusan Daun Sirsak (Annona Muricata L) Terhadap Penanganan Keputihan Pada Remaja Putri - Passe, Rosita; Ikawati, Nurul; Saleh, Syamsuryanita; Marwang, Sumarni (Madu : Jurnal Kesehatan, 2024)
Soursop leaves can be used to treat leucorrhea in women because they contain acetogenic compounds, including asimisin, bulatacin and squamosin which contain antiseptic substances the can kill germs, namely phenol, where the phenol contain in soursop leaves is 5 times more effective than ordinary phenol. This study aims to determine the effect of giving soursop leaft decoction on the management of leucorrhoea in young women at SMP MUhammadiyah 1 Makassar. This type of research used a quasi-experimental design, with the research design used pre and post test control group design. In this study the initial measurement (pretest) of the level of leucorrhoea ini young women was given bevore being given soursop leaf decoction, then a treatment was carried out (giving soursop leaf decoction) and a second measurement (post test) was carried out on the level of decrease ini vaginal discharge in young women after being given soursop leaves. Based on the results of the study with Mc Nemer analysis the value of P= 0,000 <0,05 then H0 was rejected, and Ha was accepted, it means that there is an effect of giving soursop leaves on the treatment of leucorrhoea in young women. Based on the results of the study, the research concluded that “there is an effect of giving soursop leaf decoction to the treatment of leucorrhoea in young women as evidenced by a probabitily value p= 0,000 <0,05.